Last electroweak WIMP standing: pseudo-dirac higgsino status and compact stars as future probes *Supported by NSF (PHY-1415548) and NASA ATP (NNX16AI12G). (April 2018) - Krall, Rebecca; Reece, Matthew
Abstract: Electroweak WIMPs are under intense scrutiny from direct detection, indirect detection, and collider experiments. Nonetheless the pure (pseudo-Dirac) higgsino, one of the simplest such WIMPs, remains elusive. We present an up-to-date assessment of current experimental constraints on neutralino dark matter. The strongest bound on pure higgsino dark matter currently may arise from AMS-02 measurements of antiprotons, though the interpretation of these results has sizable uncertainty. We discuss whether future astrophysical observations could offer novel ways to test higgsino dark matter, especially in the challenging regime with order MeV mass splitting between the two neutral higgsinos. We find that heating of white dwarfs by annihilation of higgsinos captured via inelastic scattering could be one useful probe, although it will require challenging observations of distant dwarf galaxies or a convincing case to be made for substantial dark matter content in ω Cen, a globular cluster that may be a remnant of a disrupted dwarf galaxy. White dwarfs and neutron stars give a target for astronomical observations that could eventually help to close the last, most difficult corner of parameter space for dark matter with weak interactions.